(untitled) - Goleman, Daniel; Daniel Goleman (Boston, Massachusetts, 2017)
A leader's singular job is to get results. But even with all the leadership training programs and "expert" advice available, effective leadership still eludes many people and organizations. One reason, says Daniel Goleman, is that such experts offer advice based on inference, experience, and instinct, not on quantitative data. Now, drawing on research of more than 3,000 executives, Goleman explores which precise leadership behaviors yield positive results. He outlines six distinct leadership styles, each one springing from different components of emotional intelligence. Each style has a distinct effect on the working atmosphere of a company, division, or team, and, in turn, on its financial performance
Keywords: Leadership; Management; Executive ability